Concentrations of legacy and emerging flame retardants in air and soil on a transect in the UK West Midlands. (April 2016) - Drage, Daniel S.; Newton, Seth; de Wit, Cynthia A.; Harrad, Stuart
Abstract: Passive air samples were collected monthly for 6 months from 8 sites along a transect of Birmingham, United Kingdom between June 2012 and January 2013. Soil samples were collected once at each site. Average concentrations of BDE-209, ΣPBDEs17:183 and ΣPBDEs in ambient air were 150, 49, and 180 pg m −3, respectively. Atmospheric concentrations of PBDEs were negatively correlated with distance from the city centre, exhibiting an "urban pulse". The average ΣHBCDD air concentration was 100 pg m −3, however concentrations were not correlated with distance from the city centre. Several emerging flame retardants (EFRs) were identified in air and/or soil samples: 2, 3, 4, 5-tetrabromo-bis(2-ethylhexyl) phthalate (BEH-TEBP), 1, 2-dibromo-4-(1, 2 dibromoethyl)cyclohexane (TBECH or DBE-DBCH), allyl 2, 4, 6-tribromophenyl ether (ATE), 2-bromoallyl 2, 4, 6-tribromophenyl ether (BATE), decabromodiphenyl ethane (DBDPE), and dechlorane plus (DP or DDC-CO). Average concentrations of BDE-209, ΣPBDEs17:183 and ΣPBDEs in soil were 11, 3.6, and 15 ng g −1 soil organic matter. PBDE concentrations in soil were higher at sites closest to the city centre, however correlations with distance from the city centre were not significant. BDEs-47 and -99 contributed more to ΣPBDEs in soil samples than air samples, but in both, the predominant congener was BDE-209. BATE was more abundant in air than soil but ATE was abundant in soil but not air. Highlights: First ambient air and soil data for emerging flame retardants in the UK. An update of PBDE levels provided 10 years after their UK ban. Data shows role of urban activity as a source of flame retardants to environment. BDE-209 levels higher in Birmingham than similar studies elsewhere. HBCDD in ambient air double levels measured 5 years previously.